PENGARUH PERPUTARAN KAS (CASH TURNOVER), PERPUTARAN PIUTANG (RECEIVABLE TURNOVER), DAN PERPUTARAN PERSEDIAAN (INVENTORY TURNOVER) TERHADAP PROFITABILITAS (STUDI KASUS PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2016) - Achmad Prasetiyo; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2018)
In general a company is established to obtain an optimum profit. Profit is a measure of company's ability to conduct business operations. The gap between activity ratio and profitability ratio is an element of the problem in this study. This study is to determine the effect of cash turnover, receivable turnover, and inventory turnover on profitability ROA. The type of this research is explanatory research, with sample 15 companies during 3 years periode of automotive sub sector, so there are 45 samples. Result and discussion: explains that cash turnover to profitability has significant value (2,879)> (2,021), receivable turnover has significant value to profitability of (4,556)> (2,021) and inventory turnover has significant value to profitability of (2,297) > (2.021). In the discussion t value is (2.021). the three variables have t value > t table, which signifies significance. While the test results of the three variables between cash turnover, receivables turnover, and inventory turnover on profitability earn high significant value. This is evidenced by the results of the F test, which obtained F value of 9.691 9.691> 3.23 F table, With a significant level of 0.000 <0.05 simultaneously between variables cash turnover, receivable turnover, and receivable turnover get a significant value to profitability, but asset turnover in 2014-2016 has decreased resulting in resulting profitability decreased. Companies are expected to better manage assets owned to be more effective and efficient so as to achieve maximum profit. In the next research is expected to increase the variables and periods in the study.